Vaigistatud kangelased. Suure isamaasõja veteranid Nõukogude Eesti tähtpäevaajakirjanduses 1944–1989 [Silenced Heroes. Veterans of the Great Patriotic War in the Anniversary Journalism of Soviet Estonia from 1944 to 1989] - Miil, Marek (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2013)
It is a common phenomenon that a state endeavours to gain recognition from the society to its policies and more prominent policy enforcers by distributing information in the public space. This article explores the implementation of the policy on veterans in Soviet Estonia with the help of print media. One of the purposes of the press in the Soviet Union was to introduce and advocate the exclusive treatment of history of the Communist Party. This included the regular commemoration of historical events considered significant by the party, e.g. the Great Patriotic War. Thus, on certain historical anniversaries, such as 9 May (anniversary of the victory over the German forces in the Great Patriotic War) and 22 September (date of the Soviet Red Army entering Tallinn in 1944), the sovietised Estonian print media was required to describe the events of a specific historical day, explain the importance of the event in view of the present and future, describe the commemoration of the event in contemporary times, as well as provide an opportunity for the war veterans to have their say.(Longer version of the current abstract is included in the article, starting from p 276.)